Information technology competency scale applied to the hospitality industry - Fernandes, A.; Alturas, B.; Laureano, R. (Smart Tourism Congress CETT Proceedings, 2016)
This article aims to validate an instrument that can measure Information Technology in the hospitality industry. The main study focused on the hotel industry and it was conducted with 216 employees of two different hotel groups in Brazil and Portugal. An instrument developed by Tippins & Sohi (2003) was translated into Portuguese and adapted for the hospitality industry. Later, an exploratory factor analysis was made in order to verify the psychometric properties of the version translated and adapted. In addition, a short-form scale version was developed. The results indicated that the scale could be reduced to nine items without compromising psychometric properties of the full-length scales. Finally, it has been found that the scale was capable of measuring differences in IT competency between groups. The results show that managers have greater IT competency than employees. Regarding the different hotel groups was noticed that they have significantly equal means for IT operations and IT knowledge. Therefore, hotels which could improve these two factors might be the ones which will be able to differentiate themselves and create competitive advantage. Theoretical and practical implications of the study are also discussed.